Multi-crops Germplasm Collection from Far Western Development Region of Nepal - Gupta, Salik R; KC, Hari B; Shah, Uma S; Mandal, Dayanand; Bhattarai, Mukund (Journal of Agriculture and Environment, 2013)
To widen the genetic base for further improvement, it is necessary to collect, characterize, evaluate and conserve multi-crops genetic resources. Collection of germplasm from unexplored area was conducted during 2011. A total of 504 samples were collected from Far-Western Development Region of Nepal including a wild species of rice Oryza ruffipogon Griff from Ghoda ghodi tal of Kailali district. A random sampling method was followed for most agricultural crops, where populations were large, and variability was deliberately sought. Sampling was from household stores and from harvested lots, together with individual sampling from fields and markets where appropriate. Greater diversity was found in rice (116) followed by soybean (38), maize (35), beans (28), cowpea (26) and wheat (24). The major achievements of these collections were recognized as the acquisition of additional variability for different multi-crop genetic resources.